Examining a Public Montessori School’s Response to the Pressures of High-Stakes Accountability - Block, Corrie Rebecca (Journal of Montessori Research, 2015)
In order to succeed in the current school assessment and accountability era, a public Montessori school is expected to achieve high student scores on standardized assessments. A problem for a public Montessori elementary school is how to make sense of the school’s high-stakes assessment scores in terms of its unique educational approach. This case study examined a public Montessori elementary school’s efforts as the school implemented the Montessori Method within the accountability era. The research revealed the ways the principal, teachers, and parents on the school council modified Montessori practices, curriculum, and assessment procedures based on test scores. A quality Montessori education is designed to offer children opportunities to develop both cognitive skills and affective components such as student motivation and socio-emotional skills that will serve them beyond their public school experiences. Sadly, the high-stakes testing environment influences so much of public education today. When quality education was measured through only one narrow measure of success the result in this school was clearly a restriction of priorities to areas that were easily assessed.